The Effect of Engklek on Improved Balance in Fourth Grade Children at Kiyonten State Elementary School 1 - Miftakhul Hudha; Arief Nur Wahyudi; Kuncoro Darumoyo (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study is to determine whether there is an effect of traditional sports on increasing dynamic balance in grade IV Kiyonten 1 State Elementary School children. The design of this research is pre-experimental with one group pre-test – post-test design, This research instrument with observation and in the form of a test Modified Bass Test of Dynamic Balance. This study will use descriptive statistical data analysis techniques and analyze them with the application of SPSS (statistical product and service solutions) IBM 25, which is to test for normality and test for homogeneity. When the data is normal, it can be continued to Test – T. After being tested for normality, it turns out that the results are not normal (rejected), therefore the search for hypotheses can be done with Statistics Non-Parametric or exact Test Wilcoxon, that Asymp. sig (2-tailed) is worth 0.001. Because the value is 0.001 pretest with post-test, it can be said that there is an effect of using treatment engklek traditional exercise on improving dynamic balance in grade IV SD N Kiyonten 1. So the study experienced an 11% increase in dynamic balance.